2018
DOI: 10.3390/en11020354
|View full text |Cite
|
Sign up to set email alerts
|

Co-Planning of Demand Response and Distributed Generators in an Active Distribution Network

Abstract: Abstract:The integration of renewables is fast-growing, in light of smart grid technology development. As a result, the uncertain nature of renewables and load demand poses significant technical challenges to distribution network (DN) daily operation. To alleviate such issues, price-sensitive demand response and distributed generators can be coordinated to accommodate the renewable energy. However, the investment cost for demand response facilities, i.e., load control switch and advanced metering infrastructur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In [6], several load levels were contained in the proposed DR (P-DR) model, while PDR and energy storage systems were treated as equals in the expansion planning model. In [7], co-planning of DG and DR equipment was carried out, where PDR was described by a linearized price-elastic DR model. The results showed that co-planning of DG and DR can minimize system costs as well as operation violations.…”
Section: A Indices δ Errsocrmentioning
confidence: 99%
“…In [6], several load levels were contained in the proposed DR (P-DR) model, while PDR and energy storage systems were treated as equals in the expansion planning model. In [7], co-planning of DG and DR equipment was carried out, where PDR was described by a linearized price-elastic DR model. The results showed that co-planning of DG and DR can minimize system costs as well as operation violations.…”
Section: A Indices δ Errsocrmentioning
confidence: 99%
“…Introducing a high penetration of DPVSs to the grid could have significant impacts on many aspects, including demand response (DR) capacity estimation [3][4][5][6], customer baseline load estimation [7,8], load forecasting [9,10] and distribution network planning [11,12]. Specifically, in terms of DR capacity estimation, the DR aggregators need to estimate how much DR capacity they have in order to formulate the reasonable bidding strategy in the electricity market.…”
Section: Background and Motivationmentioning
confidence: 99%
“…However, as the proportion of Renewable Distributed Generation connected to the distribution network, the economy and stability of the distribution network are particularly important [1][2][3][4]. With the large-scale access of DG, the traditional centralized management mode of distribution network is not applicable, and a new load scheduling method for demand side load is needed [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%